2020
DOI: 10.1016/j.annemergmed.2019.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong Versus Standard Long Peripheral Intravenous Catheters: A Randomized Controlled Trial of Ultrasonographically Guided Catheter Survival

Abstract: Study objective: Ultrasonographically guided intravenous peripheral catheters have dismal dwell time, with most intravenous lines failing before completion of therapy. Catheter length in the vein is directly related to catheter longevity. We investigate the survival of an ultralong ultrasonographically guided intravenous peripheral catheter compared with a standard long one. Methods: We conducted a single-site, nonblinded, randomized trial of catheter survival. Adult patients presenting to the emergency depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…Furthermore, the risk of catheter failure decreased by 29% for every 5% increase of catheter length located in vein. This evidence is supported by another study investigating the survival of an ultralong peripheral catheter in adults than a standard-length catheter in ultrasound guidance; it reported a markedly higher catheter survival rate when the catheter length in the vein exceeded 2.75 cm [29].…”
Section: How Do We Check the Vascular Condition?mentioning
confidence: 59%
“…Furthermore, the risk of catheter failure decreased by 29% for every 5% increase of catheter length located in vein. This evidence is supported by another study investigating the survival of an ultralong peripheral catheter in adults than a standard-length catheter in ultrasound guidance; it reported a markedly higher catheter survival rate when the catheter length in the vein exceeded 2.75 cm [29].…”
Section: How Do We Check the Vascular Condition?mentioning
confidence: 59%
“…The value of longer peripheral catheters cannot be overstated, and the increased length in-vein has been a key variable in helping transform catheter survival outcomes. [2][3][4][5] USguided venous access is no longer a form of bridge or temporary access lasting a mere 24 hours or less but now is a reliable vascular access strategy with most catheters surviving for several days to completion of therapy. The evidence now strongly supports consideration of catheter length in US PIV insertions, and the 2021 Infusion Nursing Standards was also updated to include this recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications over the last few years have shown that catheter length in-vein is a significant predictor of enhanced survival in US-guided insertions. [2][3][4][5] In 2018, Pandurangadu et al 3 prospectively investigated the relationship of catheter length in-vein and US PIV survival in a 4.78-cm PIV. The authors found that when < 30% of the catheter was in the vein, 100% of the catheters failed (median time to failure of 15.6 hours) compared with no IV failures when ≥ 65% of the catheter was in the vein.…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…3,11 Exactly why PIVC insertion is difficult in children, and the mechanisms of failure, are unknown. It is likely to be multifaceted and related to factors concerning the patient (eg, comorbidities, age, gender, adiposity), 11,12 provider (eg, insertion practice, care, and maintenance), 3,13,14 device (eg, size, length, catheter-to-vein ratio), 15,16 and therapy (eg, vessel irritation). 11,13,17 Observational studies and randomized controlled trials (RCTs) in hospitalized pediatric patients report that the average PIVC dwell is approximately 48 hours, suggesting multiple PIVCs are required to complete a single admission.…”
Section: Techniques and Technologies To Improve Peripheral Intravenous Cathetermentioning
confidence: 99%